O perfil socioeconômico das famílias do bairro Malvinas - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2014)
This article aims to analyze the socioeconomic profile of families of the Falklands neighborhood in the city of the Jari Orangery, from an analysis of categories and concepts about Morgan family, through a brief history of the structure of families in the neighborhood Falklands, how they were structured and how was the occupation of the region by major projects and what consequences this occupation has brought to families. The methodology consisted of a survey of the field, through a collection of household data, which closed questionnaires among members residing in the households surveyed were selected randomly applied. The survey results demonstrate the socioeconomic difficulties that families live without sanitation, safe drinking water and adequate sewage without schools, outpatient clinic, which further exacerbates the conditions of poverty and misery in which they live. These factors show evidence of pockets of poverty that are formed in the vicinity of large projects in the Amazon, bringing consequences for the families living there, with the need for investment and execution of public policies on sanitation that actually enable the security and permanence of these access families with on-site sanitation quality and quality public services in education, health and safety.
Keywords: Família - Perfil socioeconômico; Família - Dificuldade socioeconômica; Malvinas (Laranjal do Jari, AP); CNPQ::CIENCIAS SOCIAIS APLICADAS